Spinicaudata (Branchiopoda: Diplostraca) in Australia's Arid Zone: Unparalleled Diversity at Regional Scales and within Water Bodies. Issue 3 (1st May 2015) - Schwentner, Martin; Timms, Brian V.; Richter, Stefan
Abstract: Multispecies spinicaudatan assemblages, where several species co-occur simultaneously within the same water body, are relatively rarely observed. In part, this can be due to taxonomic impediments and the presence of cryptic species. Several recent studies on Australian Spinicaudata revealed much higher species diversities than previously known for this continent. Herein we summarize the results of three years of extensive sampling within eastern and central Australia, including 232 sampling events from 205 water bodies, and present new genetic data on Eulimnadia and Paralimnadia . Species were delimited following an evolutionary systematics framework using mitochondrial and nuclear markers to identify reproductively isolated species (biological species). Our conservative approach suggests 55 species occurring within central and eastern Australia, which raises the number to about 70 species Australia wide: one third of the known global spinicaudatan diversity. The central Paroo River catchment exhibited the largest spinicaudatan diversity ever observed on a regional scale with 31 species recorded on just approximately 60 km^2 . Diversities within water bodies are exceptionally high: half of the water bodies feature two or more species, with up to seven species and up to four congeners co-occurring simultaneously. Such diversities within water bodies have never been observed before for Spinicaudata. When a water body was sampled multiple times or when sediment samples were artificially incubated, the total species count was further increased (up to eight species). Nevertheless, most species are mutually exclusive, suggesting competition and/or restrictive habitat requirements are responsible for shaping spinicaudatan communities.